2005
DOI: 10.1097/01.blo.0000179591.72844.c3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Prognosis of Chondroblastoma

Abstract: Therapeutic Study, Level IV (case series). See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
137
3
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(155 citation statements)
references
References 9 publications
7
137
3
8
Order By: Relevance
“…We did not observe any clinically relevant growth arrest, limb length discrepancies, or malalignments as complications. Many authors have reported that tumors in the proximal femur and the pelvis are more likely to recur as a result of the difficulty in the surgical access necessary to achieve complete excision [15,18,22,24]. We have described only one proximal femur recurrence after performing a direct anterior or anterolateral approach in most cases.…”
Section: Discussionmentioning
confidence: 75%
“…We did not observe any clinically relevant growth arrest, limb length discrepancies, or malalignments as complications. Many authors have reported that tumors in the proximal femur and the pelvis are more likely to recur as a result of the difficulty in the surgical access necessary to achieve complete excision [15,18,22,24]. We have described only one proximal femur recurrence after performing a direct anterior or anterolateral approach in most cases.…”
Section: Discussionmentioning
confidence: 75%
“…However, of eight cases with functional impairment at follow-up, five involved the hip, with the other three all at different sites [1]. Lin et al noted that few patients with chondroblastoma had much growth remaining, but that four patients who had treatment before skeletal maturity had a growth plate disturbance [13]. They also reported that all patients with femoral head chondroblastomas were curetted by a cortical window in the femoral neck, but none developed avascular necrosis.…”
Section: Discussionmentioning
confidence: 97%
“…Radiotherapy is contraindicated, as there is a significant risk of inducing a malignant transformation. Recurrence rates of 10-40% have been described [1,5,9,13]. There have been rare reports of seeding into soft tissues locally, and of pulmonary metastasis in about 1% of cases [12,14].…”
Section: Discussionmentioning
confidence: 98%
“…Chondroblastoma is an uncommon benign bone tumour, which is locally aggressive [1][2][3][4], and arises from a secondary ossification centre in epiphyseal plates and apophyses [5][6][7]. Chondroblastoma accounts for approximately 1-2 % of all primary bone tumours [8].…”
Section: Introductionmentioning
confidence: 99%